Indian Draft DNA Profiling Act: Implications for Institutionalisation and Growth of Forensics (Indian Internet Journal of Forensic Medicine and Toxicology, 2018)
In the present scenario of fast developments in miniaturisation and automation of DNA sequencing/fingerprinting, the DNA-based techniques are phasing out traditional techniques in forensics like serology and microscopy in forensic biology. Although the initial cost of infrastructure and access to technology is a barrier but in long run DNA-based techniques are cost-effective at large scales and also more reliable due to higher stability of DNA compared with protein and other biomolecules. In this context, the law to be soon passed by parliament regarding DNA fingerprinting is very important for streamlining the procedures in sample collection, processing and disposal as well as building an electronic database of DNA profiles. The DNA Profiling Act shall take care of privacy and human rights concerns but its implementation will definitely be a leap forward in robust delivery of justice. Advocacy by academicians for DNA profile act may get it passed by parliament expeditiously and there is also need for more training and promotion of DNA fingerprinting and other DNA Technologies. Many countries around the world has adopted DNA profiling law long back but India is yet to pass such law despite the fact that our country needs it even more due to so many people being reported missing every year and almost equal number of unidentified dead bodies being found.
Keywords: DNA profiling act; Forensics; Implications; Indian; Institutionalisation